A theoretical analysis of food meaning in anthropology and sociology - Aktaş-Polat, Semra (Array, 2020)
The purpose of this study is to present a theoretical analysis that seeks an answer on the question of what the meanings of food are in anthropology and sociology. As a result of the analysis, it is determined that food has three main meanings (i) consumption, (ii) transfer, and (iii) identity. Moreover, six sub-meanings are found under these three main meanings. Consumption is represented by hedonic and symbolic sub-meanings, transfer is represented by culture and emotion sub-meanings, and identity is represented by personal and national identity sub-meanings. One of the reasons that make this work unique is that it defines and categorizes meanings of food in terms of individual and society. Another value added by this study is the Food Meaning Diagram (FMD) as a contribution to the literature. Furthermore, the study provides a basis for the construction of research in the related fields and to guide the studies to be carried out within the framework of human sciences.